Pengembangan Model Pembelajaran Scientific untuk Meningkatkan Kemampuan Berpikir Kritis Mahasiswa pada Mata Kuliah Belajar dan Pembelajaran - Halena M. Bekata; Adolfina M.S Moybeka; Nehemia Fanpada (Jurnal Ilmiah Wahana Pendidikan, 2021)
Learning to think is a cognitive activity that is carried out mentally to solve problems, thinking is also a process of rearranging knowledge that is cognitive. Thinking is generally considered as a person's mental process in dealing with and solving a problem. By thinking, people can solve a problem in life. Students are people who are studying in higher education so that they are considered to have high intellectuality, are intelligent in thinking and planned in acting. Learning that is knowledge transfer and memorization without requiring students to think critically and creatively causes students to not optimally have the ability to develop their ideas or concepts. This research is oriented towards the development of a scientific learning model to improve students' thinking skills. The purpose of this research is to produce a practical and effective scientific learning model design for students. R&D method with Borg & Gall procedure. The research products are Semester Learning Plan (RPS) documents and teaching materials and test instruments. Data analysis in this study uses descriptive quantitative method, comparative test 't'. The results of the validator's research on the assessment of the device showed that the category was very good. The results of data analysis related to student responses to scientific model learning tools are in the very pleasant category, meaning that 55% of students have a positive response to scientific model learning tools. The results of the comparison test of the average learning outcomes of students who study using the learning model show that the scores obtained by students after using the scientific learning model are 79.60 and the learning outcomes before using the scientific learning model are 61.30. Thus, it can be said that the student learning outcomes after using the scientific learning model is better than before.